The Effect Of The CTL (Contextual Teaching And Learning) Learning Model On Students' Learning Outcomes In The Economics Subject Of Grade XI - Damanik, Ernike Selviana; Margareta, Elisabeth; Siagian, Lasma (STABN RADEN WIJAYA WONOGIRI, 2024)
This study aims to determine the effect of the Contextual Teaching and Learning (CTL) model on students' learning outcomes in the Economics subject for Grade XI students of the Hospitality Program at SMK Negeri 8 Medan. This research is motivated by the low academic performance of students in Economics, especially in the topic of entrepreneurship. The CTL model is designed to relate the learning material to students' real-life contexts to improve their conceptual understanding in a more meaningful way. This study employed a quantitative method with a pre-experimental design using the One Group Pretest-Posttest Design. The sample consisted of 33 students from class XI PH 2, selected randomly from the population of Grade XI Hospitality students. Data collection instruments included multiple-choice tests covering the cognitive aspects of learning outcomes, which were previously tested for validity and reliability. The data analysis techniques used in this study included descriptive analysis, normality test, simple linear regression, t-test, F-test, and N-Gain analysis. The results showed a significant increase in posttest scores compared to pretest scores. The average posttest score was higher than the pretest score. The t-test result showed that tcount = 8.359 > ttable = 2.040, indicating that the alternative hypothesis is accepted. Thus, it can be concluded that the Contextual Teaching and Learning (CTL) model has a positive and significant effect on students' learning outcomes in Economics.